Exploring how human needs fulfillment shapes the perception of external catalysts to eco-behaviour - Abu Bakar, Aisyah (Malaysian Institute Of Planners, 2024)
This study explored the connection between how people perceive the external condition for environmental behaviour [EC] and meeting human needs by drawing upon Maslow’s Hierarchy of Needs [HON], Subjective Well-Being [SWB], and Human Interdependence [HI]. Research Questions: (1) Will EC increase if human needs are conveniently met? (2) Can unmet human needs lead to an increase in EC, and if so, which needs do not significantly impact EC? Purpose: This research investigates the variation in EC across the convenience and difficulty of addressing human needs. Approach: Mann-Whitney U test was conducted to measure the variation of EC across convenience and difficulty in addressing 24 human requirements. Findings: The convenience of satisfying 17 human needs led to a significant increase in EC while the other 7 human needs demonstrated no significant effect. The findings suggest that EC has the ability to develop autonomously, regardless of fulfilling human needs.